Endovascular thrombectomy for the treatment of acute ischemic stroke - Cleusa P. Ferri; Anna Buehler; Uri Adrian Prync Flato; Paulo Puglia Junior; Jefferson G. Fernandes (Arquivos de Neuro-Psiquiatria)
ABSTRACT Few patients benefit from the current standard treatment for acute ischemic stroke (AIS), encouraging the development of new treatments. Objective To systematically review the literature on the efficacy and/or safety of endovascular thrombectomy in AIS compared to standard treatment and to identify ongoing randomized controlled trials (RCTs). Method Searches for RCTs were performed in Medline/Embase, and for ongoing trials: International Clinical Trial Registry Platform, Clinicaltrials.gov and ISRCTN registry (to June 15th, 2015). Results From the eight published RCTs, five showed the superiority of treatment that includes thrombectomy compared to standard care alone. From the 13 ongoing RCTs, 3 have been halted, one has not started, one has unknown status and eight will end between 2016 - 2020. Conclusion Evidence favours a combination of the standard therapy with endovascular thrombectomy. The selection criteria however limit the number of people who can benefit. Further studies are needed to prove its cost-effectiveness.